Comparison of the traditional stock valuation models with Ohlson's valuation model - Σπηλιώτης, Σ. Ν.; Καραθανάσης, Γεώργιος Α. (SPOUDAI Journal of Economics and Business, 2002)
Traditional valuation models suggest that equity prices are determined by variables such as dividends and growth in dividends. Ohlson (1995) and Feltham and Ohlson (1995) indicate that equity prices are determined by book value and discounted future abnormal earnings. This paper uses panel data analysis and equity prices from Athens Stock Exchange in order to compare the explainability of the traditional and the more recent models of equity valuation. The results show that the explainability of the Ohlson (1995) model is quite similar to that ofthe traditional models even though in some cases Ohlson's model explainability appears to be superior. JEL Classification: Gl